2015
DOI: 10.5152/anatoljcardiol.2015.6514
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and clinical benefit of cognitive–behavioral intervention for preparing patients for transesophageal echocardiography

Abstract: Objective:Despite premedication, anxiety in patients undergoing transesophageal echocardiography (TEE) is prevalent, often causing adverse physiological and psychological effects and contributing to decreased patient compliance. We aimed to evaluate the feasibility of cognitive–behavioral intervention (CBI) in patients undergoing TEE and to assess its impact on the severity of anxiety, patient’s and physician’s comfort, and administered dose of sedatives.Methods:Our study was designed as a prospective, single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As we have previously reported in another study, appropriate preparation of patients to the TEE results in lower patient anxiety and discomfort, as well as improves comfort of the physician and reduces the dose of used sedatives [18]. Of note, none of the procedures performed by us were aborted due to lack of patient cooperation.…”
Section: A B Cmentioning
confidence: 75%
“…As we have previously reported in another study, appropriate preparation of patients to the TEE results in lower patient anxiety and discomfort, as well as improves comfort of the physician and reduces the dose of used sedatives [18]. Of note, none of the procedures performed by us were aborted due to lack of patient cooperation.…”
Section: A B Cmentioning
confidence: 75%
“…We read with great interest the article in this issue of Anatol J Cardiol entitled "Feasibility and clinical benefit of cognitive-behavioral intervention for preparing patients for transesophageal echocardiography" by Wejner-Mik et al (2), where they reported their experience on impact of cognitive behavior intervention (CBI) on the severity of anxiety, patient and physician comfort, and administered dose of sedatives in a group of patients undergoing TEE. Though subject to several limitations, their experience is certainly a turning point in preparing patients for elective TEE.…”
mentioning
confidence: 99%